The ancient Maya city of Palenque: Enlightened debate about this American indigenous antiquary - de Pedro Robles, Antonio E. (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The discovery of the ancient Maya city of Palenque (stone houses) in mid-XVIII century within the Chiapaneca forest, stated a signiicant fact in the context of the enlightened debate which will be developed in Spain and the American kingdoms and viceroyships, especially New Spain. Two critical aspects of the debate will be considered in this paper. The irst issue relates to the origin and authorship of these archaeological remains,based on two assumptions: the participation of overseas human groups in their building or inluence, or the work of indigenous communities different to those existing in the XVIII century. These groups were able to create works of extraordinary technical and ornamental intricacy. The second issue deals with the role of the creation of images by the members of the expedition and the artists who accompanied them, as well as the consequences of the process of knowledge about the American pre-Hispanicworld and its dissemination.